2013
DOI: 10.4161/cbt.25939
|View full text |Cite
|
Sign up to set email alerts
|

MK-2206, an Akt inhibitor, enhances carboplatinum/paclitaxel efficacy in gastric cancer cell lines

Abstract: Figure 4. MK-2206 synergizes with CarboTaxol in reducing anchorage-independent growth in three gastric cancer cell lines. aGs cells treated with 100 μM MK-2206, 100 nM CarboTaxol (1000:1 molar ratio of carboplatinum and paclitaxel respectively) or combination for 2 weeks. MK-2206 was re-dosed twice weekly. *The CarboTaxol and MK-2206 combination significantly reduced colony counts relative to CarboTaxol alone (unpaired t test P values were 0.002, 0.001, and 0.03 for aGs, sNU-1, and sNU-16 cell lines, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Recently, combined (rather than single‐agent) chemotherapy has been found to be a superior treatment method (Almhanna et al , ). Notably, in our previous study, a combination treatment with low‐doses of ROS inducers produces abundant ROS generation and triggers cell apoptosis (Zou et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, combined (rather than single‐agent) chemotherapy has been found to be a superior treatment method (Almhanna et al , ). Notably, in our previous study, a combination treatment with low‐doses of ROS inducers produces abundant ROS generation and triggers cell apoptosis (Zou et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown anticancer activity of MK-2206 across multiple tumor types as well as synergy with established chemotherapeutic agents in NSCLC (Agarwal et al 2014; Almhanna et al 2013; Hirai et al 2010; Konopleva et al 2014; Rashmi et al 2014). Additional work has indicated synergy and enhanced cytotoxicity when MK-2206 is combined with EGFR inhibitors including erlotinib, gefitinib, and cetuximab in the context of a limited number of NSCLC, breast, and glioma cell lines (Cheng et al 2012; Hirai et al 2010; Iida et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Now, research has proved that the AKT inhibitor could reverse the drug resistance of gastric cancer cells. 71 Further validation and application researches have been carried out and would get promising results for clinical works. 72…”
Section: Change Of Apoptosis and Autophagy Dysfunction Of Apoptosis Pmentioning
confidence: 99%